PWE-103 Participation, Positivity and Outcomes in The Nepali Community Invited for Bowel Cancer Screening – A Feasibility Study. (17th August 2016) - Seaman, HE; Snowball, J; Butler, P; Underwood, J; Bruce, H
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) offers biennial screening for all adults in England aged 60–74 years using a guaiac-based faecal occult blood test (gFOBt). This feasibility study investigated anecdotal evidence that people who originate from Nepal account for a higher than expected proportion of gFOBt-positive subjects who have a normal outcome at follow-up colonoscopy (false-positive). The BCSP Southern Hub serves several geographical areas with relatively high proportions of Nepali subjects ( e.g. Aldershot, Reading and Ashford). Methods: Data for subjects aged 60–74 invited for screening in the Southern Hub (roll-out to September 2014) were extracted from the BCSP database (BCSS). Because information about subjects' ethnicity is not recorded on BCSS, Nepali subjects were identified using an algorithm that was based on surname and postcode of residence (subject residing in an area where ≥8% of the BCSP-invited population had a Nepali surname). Data on uptake, gFOBt-positivity and false-positivity were compared between Nepali and non-Nepali men and women invited for screening. Results: We identified 5, 274 Nepali subjects (43.5% women) amongst the 6, 218, 071 subjects invited for screening during the study period. Compared with the non-Nepali population, uptake of screening was significantly higher amongst Nepalis (61.9% vs. 58.3%; odds ratio [OR] 1.16, 95% Confidence Interval [95%CI] 1.10, 1.23), more so amongst Nepali men (OR 1.26, 95%CI 1.17, 1.35) than women (OR 1.09, 95%CI 1.00, 1.19). Positivity was high in the Nepali population (7.6% vs. 2.0%; OR 4.01, 95%CI 3.53, 4.57) and higher for women (OR 5.13, 95%CI 4.22, 6.23) than men (OR 3.20, 95%CI 2.69, 3.81). False-positivity was markedly higher in the Nepali population (OR 2.37 95%CI 1.77, 3.18). More than half of gFOBt-positive Nepali women (50.6%) had a normal outcome at colonoscopy (false-positive), compared with 24.4% in non-Nepali women (OR 3.18 95%CI 2.09, 4.84). The proportion of Nepali men with a false-positive outcome was also greater than amongst non-Nepali men (OR 1.75, 95%CI 1.12, 2.75). Conclusion: Compared with non-Nepali gFOBT-positive subjects, false-positivity was high in the Nepali community living in the south of England. The reasons for high false-positivity, implications for colonoscopy resource and exposure of subjects to unnecessary risk will be addressed in further work. The study area will be extended to include other Nepali communities living in London and a validation exercise will be undertaken to test the algorithm used to identify Nepali subjects. Disclosure of Interest: None Declared